RELIGIUSITAS, SPIRITUALITAS DALAM KAJIAN PSIKOLOGI DAN URGENSI PERUMUSAN RELIGIUSITAS ISLAM - Fridayanti Fridayanti (Psympathic : Jurnal Ilmiah Psikologi, 2015)
The debate about the religiosity definition is still going on until now. The religion psychologist have not a consensus yet about the religiosity definitiont. It impacted in doubt about the use of the existing religiosity scale. Some attempts in explaining religiosity from the Islamic perspective has been done by some psychologists from the Islamic world. This article attempts to explain the cause of lacking consensus regarding the notion of religiosity through study on conception of religiosity in the West’s understanding, as well as efforts that have been made by the Islamic world in making the formulation regarding concept of the Islamic thought and traditions including criticisms and suggestions for further development of the notion religiosity to be used in the Muslim community.